O direito criminal pós-positivista e o devido processo penal constitucional - Balico, Vladimir (2008)
This paper examines the hermeneutics of under criminal law in the light of the Federal Constitution, in a State Constitutional and Democratic of law, which has the idea synthesis human dignity. The idea of Justice goes by the concept of proportionality, valley Say, there is no possible interpretation out of the constitutional text, especially in criminal matters, which assigns to each what it is due, in Measure of its labors, which is made without the weighting of the values at stake, goods criminally clients. It is therefore to leave the as merely interpretation. Taking as Principles the State Constitutional and Democratic Right, and also to human dignity, All hermeneutics, held from and the Federal Constitution is performed considering the human person as the centre of the legal system. Every system of interpretation is, destarte, for human dignity. It was, of another band, demonstrate the constitutional structure, Principles and rules so that they exclude those and if incorporate. The constitutional architecture remains thus present and functioning, Dispensing to his amendment. It is what can be called the neo-positivism. The principles, since then, are vital In the preparation, implementation and exegesis in the criminal sphere. It follows that the correct application of the criminal law can not refrain from considering the well Legal constitutionally guaranteed, under penalty of unconstitutionality, or rather injustice. Raised condition of the core of the guardianship Constitutional, and legal - and, consequently, their protection vodi all activity of the criminal sphere, since the election of the criminal path For combating social instability given to the implementation criminal conduct as a result of the attack and managed criminally. Also ofencivity took the vital importance as a criminal. The Federal Constitution itself provides a link between the order sought by State and the means to be used to achieve it. The idea of designating Constitution thus the purpose of the rule the-Justo while laws. Are the means by which it seeks the establishment of justice. Acresça to that framework international treaties on human rights erected, By the Magna Carta, the fundamental rules apply immediately. The so-called post-positivism is enriches, also, with the assumption of Dignity of the human person at the center of the law, as constitutional protoprincípio of hermeneutics